Root interactions between young Eucalyptus deglupta trees and competitive grass species in contour strips - Schaller, Michaela (Forest Ecology and Management, 2020)
To reduce soil erosion on sloping fields grass strips are commonly planted on the contours. The integration of timber trees into such strips can be economically beneficial and at the same time increase the anti-erosion effect of the strips. Root competition between grasses and trees within such strips may affect tree development, but might also reduce root competition between the trees and adjacent field crops if the grass strips restrict the lateral development of the tree root systems. The present experiment, carried out on a fertile site (Aquandic Dystrudept) in a high-rainfall region in Costa Rica (2700 mm per year), was designed to evaluate whether the lateral extension of the root system of Eucalyptus deglupta could be restricted by strips of the grasses Panicum maximum, Brachiaria brizantha or Saccharum officinarum, planted either in single, double- or triple-rows on both sides of rows of the trees. E. deglupta growth was significantly reduced in the association with P. maximum, the most competitive grass species, and to a lesser extent, by the double- and triple-row B. brizantha strips. In these treatments, the total number of lateral tree roots, as evaluated in profile walls, was reduced by up to 40% compared to the no-grass control. Furthermore, the lateral restriction of the tree root systems led to an increased density of tree roots between the grass strips. S. officinarum did not reduce the total number of tree roots and only slightly restricted lateral tree root extension. Grass strips composed of multiple grass rows appeared to restrict lateral tree root development more than strips with single grass rows but this effect was not statistically significant. None of the grasses forced the tree root systems to develop at a greater depth; on the contrary, tree roots were more superficial in the profiles beyond as well as between the grass strips in comparison to the no-grass control. There was some evidence of an increased root barrier effect of the grass strips in areas with a compacted topsoil. The barrier effect tended to decrease with increasing age of the trees. These results suggest that strips of competitive grasses can reduce the lateral root development, especially of young trees, when planted in contour strips, and this may reduce and/or delay root competition with neighboring field crops. The observed trends are likely to change as trees grow older and longer-term studies are needed. © 2002 Elsevier Science B.V. All rights reserved.